2017
DOI: 10.1007/s11414-017-9562-y
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Perspective in Mental Health Services Use Among Adults with Mental Disorders

Abstract: This study examined factors associated with mental health services (MHS) use by individuals with mental disorders within a developmental perspective of adulthood. Bivariate and multivariate analyses were conducted separately for each developmental stage on independent variables using the Andersen's behavioral health service model. For 18-29-year-old emerging adults (n = 141), autonomy, daily life/relations, Internet searching, alcohol dependence, cognitive impulsiveness, number of stressful events, and self-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…The 50-year threshold was determined based on an adult's developmental perspective, where middle-aged adulthood (50 to 64 years old) usually begins. 36,37 This period also coincides with menopause in women, and a higher prevalence of chronic illnesses, especially cardiovascular illnesses. 38,39 The Material Deprivation Index, based on the smallest dissemination areas established for the 2011 Canadian census, integrated ratios of population employment, average income, and education levels lower than high school, while the Social Deprivation Index included proportions of patients living alone, those whose civil status is “single,” and single-parent families.…”
Section: Methodsmentioning
confidence: 99%
“…The 50-year threshold was determined based on an adult's developmental perspective, where middle-aged adulthood (50 to 64 years old) usually begins. 36,37 This period also coincides with menopause in women, and a higher prevalence of chronic illnesses, especially cardiovascular illnesses. 38,39 The Material Deprivation Index, based on the smallest dissemination areas established for the 2011 Canadian census, integrated ratios of population employment, average income, and education levels lower than high school, while the Social Deprivation Index included proportions of patients living alone, those whose civil status is “single,” and single-parent families.…”
Section: Methodsmentioning
confidence: 99%
“…Mental health issues and factors impacting service use differ based on the specific biological, social, age‐related, and identity‐based changes during a developmental stage (Huỳnh et al, 2018; Patton et al, 2016) and must be considered to improve CAMH. For example, as many as three quarters of all mental disorders begin during adolescence (Jones, 2013; Thapar & Riglin, 2020), including anxiety disorders, obsessive and compulsive disorders, and eating disorders (Solmi et al, 2021).…”
Section: Developmental Perspective Of Camhmentioning
confidence: 99%
“…As such, a developmental approach to CAMH must consider the biopsychosocial needs and contexts of both children and adolescents, especially in K-12 schools (Avison, 2010). Indeed, Huỳnh et al (2018) found that practices that increase help-seeking behaviors differ among developmental stages, and so strategies to improve CAMH access must adapt to these changing needs.…”
Section: Developmental Perspective Of Camhmentioning
confidence: 99%
“…Thus, studying mental health symptoms across stages of the pandemic is critical to understanding whether symptoms persist. In addition, from a developmental perspective, young adults are in a highly transitional stage in the life course during which they establish long-term relationships, raise children, establish careers, buy homes and build financial security 21 , 22 . Given 75% of mental health disorders have a first onset before age 25 23 , empirical evidence highlighting vulnerability to the effects of COVID-19 among young adults with history of mental health disorders is warranted.…”
Section: Introductionmentioning
confidence: 99%